INTERNALISASI DAN AKTUALISASI BUDAYA KEDISIPLINAN DI MTS AL-ISLAM JORESAN DALAM MEMBENTUK KARAKTER SISWA - Mustofa, Zamzam; Beauty, Amalia Rifanda; Prastio, Eko; Fitiya, Hasni; Nisaurrohmah, Nida; Prayitno, Mustofa Aji (UII Darullughah Waddawah Pasuruan, 2023)
MTs Al-Islam Joresan applies a strong commitment to improving student character through a discipline that is implemented in various forms of programs and activities both inside and outside the classroom. This study aims to determine the efforts made by educational institutions and teachers at MTs Al-Islam Joresan in guiding student discipline and how it impacts the formation of student character. This study uses a qualitative research approach with data analysis techniques which include data reduction, data presentation, and drawing conclusions. The results of the data analysis will be used to answer the problems raised in the research. The results of the study show that the implementation of discipline carried out at MTs Al-Islam Joresan can be divided into two categories, namely discipline in the classroom and discipline outside the classroom. In addition to supporting the character development of its students, MTs Al-Islam Joresan also organizes outreach programs in the form of class and non-class programs, organizes various extracurricular programs that can support student character development, and encourages students to actively participate in religious and social activities both at school as well as in the community.